Dementia case-finding in acute hospitals: a qualitative study of perspectives of hospital clinicians and general practitioners. (November 2016) - Burn, Anne-Marie; Bunn, Frances; Fleming, Jane
Abstract: Background: Concerns about hospital care of older people with dementia have led to UK Department of Health targets for acute hospitals to identify patients who could have dementia. Although dementia does not fit screening programme criteria, this requirement for dementia case-finding (DCF) reflects policy drives encouraging earlier diagnosis. Hospitals have set up their own processes to conduct assessments on all people aged 75 years and older with unplanned hospital admissions longer than 72 h and inform general practitioners (GPs). The potentially far-reaching effects are unknown. The Cascade study is exploring how hospitals across the East of England are implementing DCF, how results are communicated to GPs, and the impacts on patients and their subsequent care. We aimed to describe current DCF practice and to understand perspectives of both primary and secondary care clinicians on objectives, challenges, barriers, and perceived benefits of DCF. Methods: We conducted topic-guided telephone interviews and focus groups with relevant health-care professionals contacted through multiple strategies. Direct e-mail invitations to hospital staff including Trust dementia leads and nurse specialists and invitations to GPs circulated through clinical and research networks, primary care services, and local GP forum meetings aimed for a purposive sample representing hospitals across the East of England. Anonymised transcripts were analysed with a framework approach. Findings: We undertook interviews and focus groups with 23 hospital staff and 36 primary care staff (including 30 GPs). Hospitals differed in their approaches to DCF in terms of how, when, and by whom cognition was assessed and ways in which DCF outcomes were recorded and communicated to GPs. Although hospital IT systems were set up to ensure DCF completion, non-compliance could be a problem, especially within specialties where DCF was not a priority. Overall, staff in secondary care were more positive than were those in primary care about the benefits of DCF, including its awareness-raising, although there were concerns about impacts on resources and workload. GPs raised concerns about duplication of effort, the lack of an evidence-base for DCF, lack of access to information, limited post-diagnostic support services, and the appropriateness of DCF in the hospital setting. Interpretation: Preliminary findings re-affirm that policies affecting public health need implementation that allows evaluation to inform the evidence-base. Funding: National Institute of Health Research Collaboration for Leadership in Applied Health Research and Care East of England